Brain disorders associated with corticotropin‐releasing hormone expression in the placenta among children born before the 28th week of gestation. (13th November 2015) - Leviton, Alan; Allred, Elizabeth N.; Kuban, Karl C.K.; O'Shea, Thomas Michael; Paneth, Nigel; Majzoub, Joseph
Abstract: Aim: To evaluate the relationship between placenta corticotropin‐releasing hormone (CRH) expression and brain structure and function abnormalities in extremely preterm newborns. Methods: In a sample of 1243 infants born before the 28th week of gestation, we evaluated the relationship between CRH expression in the placenta and the risk of brain ultrasound scan abnormalities identified while these infants were in the intensive care nursery, low scores on the Bayley Scales of Infant Development‐II of 900 of these children at age two years and head circumference measurements then more than one and two standard deviations below the mean. Results: Infants who had a low placenta CRH messenger ribonucleic acid (mRNA) concentration were at increased risk of ventriculomegaly on an ultrasound scan. An elevated placenta CRH mRNA concentration was associated with increased risk of an inability to walk at age two years, and a Bayley Motor Scale 3 standard deviations below the mean. Conclusion: Placenta CRH mRNA concentration appears to convey information about the risk of brain damage in the infant born at an extremely low gestational age.